Synthesis and Antiplatelet Activity of 4-Hidroxy-3-Methoxycinnamic Acid - Erika Christy Marentek; Tutuk Budiati; Juni Ekowati (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Cinnamic acid and its derivatives have been widely studied for their efficacy because of the pharmacological effect on good health and well being. Microwave irradiation is more time effective to synthesize than conventional heating method because it conducts heat faster and shortens the reaction time.  Objective: This study aimed to synthesize 4-hydroxy-3-methoxycinnamic acid using microwave irradiation and its antiplatelet activity by blood clotting time method. Methods: Synthesis of 4-hydroxy-3-methoxycinamic acid with malonic acid and 4-hydroxy-3-methoxybenzalehyde as a starting material using ammonium acetate catalyst with microwave irradiation (960 Watt, 4 minutes). The synthesis results were tested for purity by thin-layer chromatography, a melting point determination and structure identification (UV-Vis, infrared, and proton NMR spectrometry). The antiplatelet activity test consisted of a negative control group CMC-Na, a positive control acetosal, cinnamic acid, and 4-hydroxy-3-methoxycinnamic acid, each group consisted of 3 different doses, namely 0.0037 mmol/Kg (I), 0.0069 mmol/Kg (II) and 0.0139 mmol/Kg (III). Results: Synthesis of 4-hydroxy-3-methoxycinamic acid had a yield percentage of 30.55%. The test results showed that the 4-hydroxy-3-methoxycinnamic acid compound has antiplatelet activity with an ED30 value of 1.3080 mg/Kg BW and antiplatelet activity comparable to acetosal. Conclusion: 4-hydroxy-3-methoxycinamic acid can be synthesized by microwave irradiation and had antiplatelet activity 1.7 fold greater than cinnamic acid.